Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.analchem.7b04600
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Tricarboxylic Acid Metabolites in Exhaled Breath

Abstract: The tricarboxylic acid (TCA) cycle is one of the most important metabolic pathway for cellular respiration in aerobic organisms. It provides and collects intermediates for many other interconnecting pathways and acts as a hub connecting metabolism of carbohydrates, fatty acids, and amino acids. Alteration in intracellular levels of its intermediates has been linked with a wide range of illnesses ranging from cancer to cellular necrosis or liver cirrhosis. Therefore, there exists an intrinsic interest in monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…Therefore, the water with 0.1% formic acid ( v / v ) condition was selected for optimizing further parameters. It has been reported that electrosprays of pure solvents can efficiently ionize gas-phase analytes, and several types of electrospray solutions such as water and methanol have been used for various studies [ 30 , 31 , 32 ]. An earlier study by Sinues et al [ 33 ] examined the efficiency of nano-electrospray ionization using three types of spray solvents, including water, water/methanol (1/1), and methanol, to measure amine-containing compounds such as dimethylamine, ethylamine, and trimethylamine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the water with 0.1% formic acid ( v / v ) condition was selected for optimizing further parameters. It has been reported that electrosprays of pure solvents can efficiently ionize gas-phase analytes, and several types of electrospray solutions such as water and methanol have been used for various studies [ 30 , 31 , 32 ]. An earlier study by Sinues et al [ 33 ] examined the efficiency of nano-electrospray ionization using three types of spray solvents, including water, water/methanol (1/1), and methanol, to measure amine-containing compounds such as dimethylamine, ethylamine, and trimethylamine.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 0.01% and 0.1% formic acid concentrations in water were chosen as the optimized and least optimized conditions for VFA analysis, respectively, in the later part of this study. Previously, several types of additives, including formic acid, acetic acid, and ammonium formate, have been used to facilitate the interactions between analytes and electrospray charged droplets to enhance the sensitivity of SESI analysis [ 30 , 32 , 34 ]. It has been proposed that gas-phase analytes could be charged by contacting either electrospray droplets or protons that are generated after the droplets have evaporated [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of the features typically detected by SESI-HRMS in human breath remain to be positively identified. However, over the last years, we have made a substantial effort to systematically identify the molecular structure for some of these metabolites by combining real-time breath MS/MS analysis and UPLC-MS/MS analysis of exhaled breath condensate [47][48][49][50][51][52][53]. Given the clinical importance of aldehydes, as potential surrogates of oxidative stress [54][55][56][57][58][59], we will concentrate in discussing our findings for a series of three classes of fatty aldehydes [48]: 4-hydroxy-2-alkenals (C x H 2x -2 O 2 ), 2-alkenals (C x H 2x − 2 O), and 4-hydroxy-2,6alkadienals (C x H 2x − 4 O 2 ) with chain lengths ranging from C 8 to C 16 .…”
Section: Resultsmentioning
confidence: 99%